From Ethical Naturalism to Aquinas’ Notion of Natural Law: A Non-Trivial Convergence? - Mariano Asla; María Soledad Paladino (Religions)
Is it possible for Aquinas’s moral theology to engage constructively with contemporary moral naturalism? The proposed question has already been a subject of scholarly interest, eliciting various responses. Some authors emphasize the difficulties and contradictions, while others identify potential affinities. This paper explores the extent to which Aquinas’s concept of Natural Law might align, albeit partially, with a form of moral non-reductive, non-non-cognitivist ethical naturalism. Specifically, it aims to assess how his view of Natural Law, rooted in practical reason and natural inclinations, incorporates a teleological understanding of nature, which provides a foundational basis for this consonance. Within this framework, moral virtue emerges as central in bridging bio-psychological facts with ethical principles. Aquinas’s assertion that gratia non tollit naturam, sed perficit “grace does not destroy nature but perfects it” (ST I. q1. a8) further underscores the continuity between nature and normativity, suggesting that while grace and revelation introduce true novelty, they enhance rather than supplant the natural moral order.